Una nueva técnica para el estudio microscópico de los huevos de anopheles (1947)
A new method is described for dissection and mounting of the exochorion of Anopheles eggs, for microscopic study, which has advantages over previous methods. The possible taxocomic importance of the morphology of the micropyle, clearly seen by this method, is noted.